Pharmacological effects of a new soluble guanylate cyclase stimulator in experimental pulmonary arterial hypertension - V. V. Bykov; A. V. Bykova; S. A. Stankevich; O. I. Aliev; A. V. Sidekhmenova; O. I. Dunaeva; V. A. Khazanov; A. I. Vengerovskii; V. V. Udut (Бюллетень сибирской медицины)
Aim. To assess the effect of an indolinone derivative (2-[2-[(5RS)-5-(hydroxymethyl)-3-methyl-1,3-oxazolidine-2yliden]-2-cyanoethylidene]-1H-indole-3(2H)-one (codename – GRS) on right ventricular contractility, endothelial vasodilator function, and histologic changes in the lungs and heart in a rat model of monocrotaline-induced pulmonary hypertension.Materials and methods. Pulmonary arterial hypertension (PAH) was induced in Wistar rats by a single subcutaneous administration of monocrotaline at a dose of 60 mg / kg. Starting from day 15 after PAH induction, the rats received either GRS at a dose of 10 mg / kg or riociguat at a dose of 1 mg / kg orally once a day. Blood pressure in the right ventricle, right ventricular weight, endothelial vasodilator function, and the histologic structure of the lungs and heart were studied after the last administration of test substances.Results. Twenty-eight days after monocrotaline administration, the rats developed PAH, as shown by the increase in the maximal blood pressure in the right ventricle and the right ventricular weight / total heart weight ratio. GRS after multiple administration reduced the maximal blood pressure in the right ventricle, had no significant effect on its contractility, improved endothelial vasodilator function, and normalized blood pressure. Riociguat had a hypotensive effect and did not alleviate endothelial dysfunction in experimental PAH.Conclusion. The indolinone derivative GRS and riociguat, both soluble guanylate cyclase stimulators, lowered blood pressure in the right ventricle. GRS also alleviated endothelial dysfunction in animals with experimental PAH.